STANDARDIZATION OF KADAMBA (ANTHOCEPHALUS CADAMBA(ROXB.)MIQ LEAF W.S.R. TO ITS PHARMACOGNOSTICAL EVALUATION (AYUSHDHARA, 2019)
In today’s world, the demand for herbal products is growing exponentially throughout the world due their potentiality and less side effects. Major pharmaceutical companies are currently conducting extensive research on plant materials for their potential medicinal value. Growing demand, the market value and the lack of quality of raw materials which affects the safety and efficacy created the need for standardization and critical evaluation of the herbal drugs. Kadamba is one of the important plant which is possessing many of medicinal properties. It is useful in disorders like Medoroga, Prameha, Graharogas, Vrana, Atisara, Grahani, Ashmari, Mutrakrchra etc. This article highlights the importance of standardization of Kadamba (Anthocephalus Cadamba (Roxb.) Miq) leaf considering Pharmacognostical evaluation including its Macroscopic identification, Microscopic, Organoleptic characters, Powder microscopy, Physicochemical analysis, Extractive values in solvents like aqueous, Ethanol, Methanol, Chloroform, Phytochemical analysis in various solvents, TLC and HPTLC for Aqueous and Alcohol extracts are done in Telangana State Level Drug Testing Laboratory and Dravyaguna department Dr.BRKR Govt Ayurvedic college, Hyderabad as per the guidelines laid down in Ayurvedic Pharmacopoeia of India. This study of Kadamba leaf can serve as a preliminary step towards its standardization emphasizing the need of further research.